Inheritance and development of national elements in contemporary Chinese, American and Russian oil paintings - Yang, Guangyu (Linguistics and Culture Review, 2021)
When speaking of semiosis of the visual art it is worth noting that it can be considered also in the aspect of semantics, which studies relation of sign elements to the world. Semantic side of an image is related to theory of art content, meaning of creation, spirituality, in particular, the symbol theory. Together with forming the idea of painting as a source of literature data and accordingly understanding of a painting in traditional literature paradigm as source of learning the outside world. The authors of the article demonstrate solidarity of oil painting in the stylistic understanding of the integrity of the image perception through the method of knowledge. In particular, the connection between figurativeness and semeiotics, which arises in the process of painting learning on the basis of literature researching and forming of artistic taste. In the article, it is shown that development of figurativeness in art should be based on art methods, in which literature is defined. Authors clarify that this is the main difference between Chinese painting and similar cultural forms. Practical application of research may be: to form educational programs and develop in integral image of artistic development.